PENINGKATAN KOMPETENSI GURU MELALUI PEMANFAATAN TEKNOLOGI INFORMASI [TEACHER COMPETENCE ENHANCEMENT THROUGH USE OF INFORMATION TECHNOLOGY] - Ni Ketut Dewi Ari Jayanti; Gde Sastrawangsa; Ni Made Dewi Kansa Putri (Jurnal Sinergitas PKM & CSR, 2021)
During the COVID-19 pandemic, teaching and learning activities in Indonesia, from basic education to university levels, must be carried out online. The main problem experienced by teachers in online teaching and learning activities is the lack of mastery of technology by teachers. Based on this, it is necessary to conduct mentoring and training programs to improve the ability of teachers to use technology to support online teaching and learning activities. For this reason, in this community service activity, training has been carried out which aims to provide knowledge to teachers to improve teacher competence using information technology. The method of implementing activities is through counseling and training. Activities have been evaluated using a questionnaire, the results achieved are 90.77% of teachers can use information technology to support online teaching and learning activities. BAHASA INDONESIA ABSTRACT: Pada masa pandemi COVID-19 kegiatan belajar mengajar di Indonesia, mulai dari tingkat pendidikan dasar hingga perguruan tinggi harus dilaksanakan secara daring. Permasalahan utama yang dialami oleh guru dalam kegiatan belajar mengajar daring adalah kurangnya penguasaan teknologi oleh guru. Berdasarkan hal tersebut, perlu dilakukan program pendampingan dan pelatihan untuk meningkatkan kemampuan guru-guru dalam menggunakan teknologi guna mendukung kegiatan belajar mengajar daring. Untuk itu, pada kegiatan pengabdian masyarakat ini telah dilakukan pelatihan yang bertujuan memberikan pengetahuan kepada guru-guru untuk meningkatkan kompetensi guru melalui pemanfaatan teknologi informasi. Metode pelaksanaan kegiatan melalui penyuluhan dan pelatihan. Kegiatan telah dievaluasi dengan menggunakan kuesioner, hasil yang dicapai adalah 90.77% guru dapat menggunakan teknologi informasi dalam mendukung kegiatan belajar mengajar daring.